Inserción laboral del contador titulado en el COHORTE 2015 de la Universidad Técnica de Cotopaxi. - Males Lema, María Laura (2018)
The main objective of this research was to analyze the labor insertion of the graduates of the cohort 2015, Accounting and Audit Career of the Faculty of Administrative Sciences, of the Technical University of Cotopaxi. The work was carried out in Latacunga city, in 2018. Methodologically, the analytical descriptive method was used, quantitative field. The sample was selected through the statistical formula, the data was collected through a survey which was created in Gmail Drive sent by emails, Facebook and phone calls were also made. The population was 172 graduates and 84 companies which were selected according to the sample to 49 people and 39 companies. The main results show that, if there are difficulties in finding a well-paid job, it is possible to find areas of opportunity for accountants since 84% of them are immersed in the labor market, 51% were integrated during their studies and the most of them work in related areas, with a salary less than $ 1,000 per month. The 82% of people say that they are in line with the training received by their career. It is necessary to present the analysis results to the corresponding authorities for the taking of pertinent decisions about the solution to the problem for the benefit of the new accountants and an efficient follow-up of the graduates in order to outline alternatives and match them with the demands of the modern market.